Whirlwind - Hake, Cathy Marie (Bethany House, 2008)
As a nanny, Millicent Fairweather poured her energy and talents into the two young charges under her care--only to have them suddenly and without explanation sent to a boarding school. Bereft and unsure of where life will lead her, she agrees to accompany her sister and brother-in-law to America. They board the Opportunity, confident a better life awaits. Widower Daniel Clark determines to begin life anew in Gooding, Texas, operating a mercantile. But when his nanny leaves him stranded aboard the ship with his young son, he finds himself in dire need of assistance. Obtaining temporary help from steerage, Daniel is initially taken aback by the pretty bundle of energy who takes over his suite. Yet Miss Fairweather's unique child-rearing techniques and tireless devotion to his son soon win him over. When tragedy ensues and a whirlwind decision is made, Daniel and Millicent's lives irrevocably intertwine. Will love soon follow?--From publisher description.